Pelatihan Emotional Intelligence untuk Meningkatkan Caring Behavior pada Caregiver Lansia - A.A.Ayu Wulan Dwi Anggaswari; Ni Luh Gede Puji Astiti B; William Hadi Saputro (Faculty of Ushuluddin and Humanities, 2021)
Emotional Intelligence training has been designed to increase knowledge and skills related to Caring Behavior. This training focuses more on how the caregiver recognises, understands, and manages the emotions while assisting the elderly. This training was attended by 21 elderly caregivers at Yayasan X, Surabaya. The training consists of 6 sessions given in the form of lecturing, paper and pencil, games, videos, sharing, discussion, and roleplay. The research design was one group pre-test post-test design. The assessments that have been used are interview, observation Emotional Intelligence and Caring Behavior scales. Based on the analysis that has been done, it shows that there is no significant difference related to Emotional Intelligence and Caring Behavior of participants before and after the training was given (p> 0.05). In the evaluation of knowledge, there was a difference (p<0.05) indicated by 11 participants who experienced an increase in categories. The results of the Follow Up also support this result. Namely, participants can receive and understand well the presented material and try to practice it when accompanying the elderly. Based on these results, it can be concluded that Emotional Intelligence training is quite effective in improving Caring Behavior in elderly caregivers.